Policies for Combating Illegal Fishing Crimes in Indonesia: A Comparative Study - Razak, Abdul Kamil; Suhardini, Eni Dasuki; Chalil, Sri Mulyati; Durahman, Dani (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Indonesia is an archipelago with an area of 5.8 million square kilometers of marine area and has a tremendous amount of fisheries wealth. However, fisheries in Indonesian seas are often the target of illegal fishing from foreign fishermen. To address this problem, the government has issued various very progressive policies. However, illegal fishing crimes still occur frequently.Purposes of the Research: This research aims to discuss the eradication of illegal fishing crimes in Indonesia from the perspective of Indonesian positive law and Islamic law. This research analyzes several illegal fishing cases that have been decided by the court by applying the ship confiscation penalty as a form of progressive punishment in combating illegal fishing.Methods of the Research: This study used a normative method with a comparative approach between Indonesian positive law and Islamic law.Results of the Research: The results showed that the government made a policy by setting up Task Force 115 based on Presidential Regulation Number 115/2015 on the Illegal Fishing Eradication Task Force, which is authorized to prevent and take legal action against illegal fishing criminals. The government issued Law Number 45/2009 on Fisheries jo. Law Number 11 of 2020 on Job Creation (Fisheries Cluster) by applying criminal penalties and administrative penalties. In addition, the government implemented a policy of destroying fishing equipment and foreign fishing boats by submerging them to the ocean. Regarding Islamic law, the policy of combating crime (jarimah) of illegal fishing is also mandated to the government or ruler in a country (ulil amri) because jarimah illegal fishing was classified as jarimah ta`zir. Similarly, the regulation for illegal fishing crimes in which the regulation of law enforcement mechanisms and the types of penalties to be applied are fully determined by the ruler or the state.